2019
DOI: 10.1186/s10194-018-0952-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of onabotulinumtoxinA treatment in patients with and without allodynia: results of the COMPEL study

Abstract: BackgroundOnabotulinumtoxinA is effective in treating chronic migraine (CM), but there are limited data assessing how allodynia affects preventive treatment responses. This subanalysis of the 108-week, multicenter, open-label COMPEL Study assessed the efficacy and safety of onabotulinumtoxinA in people with CM with and without allodynia.MethodsPatients (n = 715) were treated with onabotulinumtoxinA 155 U every 12 weeks for 9 treatment cycles. The Allodynia Symptom Checklist was used to identify patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…In the clinical setting, sensory features in PTH are both prominent and clinically actionable (34) aspects of headache-related disease burden. Importantly, our data highlights the presence of multimodal sensory hypersensitivity in non-migraine type, as well as in migraine-like, PTH subjects (Figures 2 and 3(c)).…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical setting, sensory features in PTH are both prominent and clinically actionable (34) aspects of headache-related disease burden. Importantly, our data highlights the presence of multimodal sensory hypersensitivity in non-migraine type, as well as in migraine-like, PTH subjects (Figures 2 and 3(c)).…”
Section: Discussionmentioning
confidence: 99%
“…Another group found that the plasma level of CGRP was higher in responders compared to non-responders, and a decrease of CGRP by treatment could also be demonstrated [134,135]. On the other hand, the presence of cutaneous allodynia did not prove to be a predicting factor for the efficacy of BoNT/A, even though it is considered to reflect the presence of central sensitization [132,133,136]. A recent study on Korean patients also suggested that longer disease duration could be associated with a poorer response [137].…”
Section: An Overview Of Clinical Evidence Of Bont/a Analgesic Effimentioning
confidence: 99%
“…In other analyses of BoNT/A efficacy in COMPEL [ 16 , 27 – 37 ] (post hoc [ 27 , 35 , 36 ], where stated): Assessments of migraine-related disability (MIDAS score) [ 28 ] and migraine-specific HR-QOL (all three MSQ domain scores) were improved ( p < 0.0001 vs baseline) at week 108 [ 28 ] Comorbid symptoms of depression [measured using the 9-item Patient Health Questionnaire (PHQ-9)] and anxiety (7-item Generalized Anxiety Disorder Assessment), and associated symptoms of sleep disturbance (Pittsburgh Sleep Quality Index) and fatigue (Fatigue Severity Scale), were improved ( p < 0.0001 vs baseline) at week 108; similar improvements were seen at all earlier assessments [ 29 ] Assessments of headache symptoms [ 16 , 30 34 ], headache-related impact (HIT-6 score) [ 16 , 30 , 33 ], migraine-related disability (MIDAS score) [ 31 , 32 , 34 ] and migraine-specific HR-QOL (all three MSQ domain scores) [ 32 , 34 ] were improved to a similar extent in patients with or without a history of acute medication overuse [ 30 , 31 ], those receiving or not receiving oral preventive treatments at baseline [ 16 ], those with or without daily headaches at baseline [ 32 , 33 ], and those with or without allodynia at baseline [ 34 ] The proportion of monthly headache-day frequency responders progressively increased over the course of the study (47%, 54%, 57% and 62% at weeks 24, 60, 84, 108, respectively). Among patients who completed all nine treatment cycles, a high proportion (76%) of monthly headache-day frequency responders at week 24 maintained this response through week 108 [ 35 ] Responder rates at week 108 were 62% for monthly headache-day frequency, 59% for HIT-6 score, 75% for MIDAS score and 66% for MSQ RR domain score; 87%, 72%, 52% and 27% of patients achieved at least one, at least two, at least three or all four of these outcomes, respectively [ 27 ] The proportion of patients who achieved treatment-controlled CM (defined as < 15 headache days/month in any of the 4-week periods ending at weeks 24, 60, 84 and 108) was high and increased progressively over the course of the study (56%, 69%, 70% and 74% at weeks 24, 60, 84 and 108, respectively) [ 36 ] Sustained treatment-controlled CM (defined as &...…”
Section: What Is the Clinical Efficacy Of Onabotulinumtoxina In Chronmentioning
confidence: 99%
“…Assessments of headache symptoms [ 16 , 30 34 ], headache-related impact (HIT-6 score) [ 16 , 30 , 33 ], migraine-related disability (MIDAS score) [ 31 , 32 , 34 ] and migraine-specific HR-QOL (all three MSQ domain scores) [ 32 , 34 ] were improved to a similar extent in patients with or without a history of acute medication overuse [ 30 , 31 ], those receiving or not receiving oral preventive treatments at baseline [ 16 ], those with or without daily headaches at baseline [ 32 , 33 ], and those with or without allodynia at baseline [ 34 ]…”
Section: What Is the Clinical Efficacy Of Onabotulinumtoxina In Chronmentioning
confidence: 99%